A device for simulating the thermoregulatory responses of the foot - Babič, Mitja (Strojniški vestnik, 2008)
A sweating thermal foot manikin was developed for evaluating the thermal and evaporative resistance of footwear. The sweating thermal foot manikin can be programmed to simulate physiological patterns of conductive, convective and evaporative heat loss. The manikin can simulate the initiation and magnitude of human non-evaporative and evaporative heat loss based on core and skin temperatures. The system comprises a computer controlled system for regulating the heaters in each of the 16 segments of the foot, as well as the sweating function provided by peristaltic pumps. Each of the 16 segments is autonomous: its heating and sweating responses are controlled independently, thus the calculation of the heat exchange can also be determined for each segment separately. Results of the footwear evaluation were compared to the results obtained for identical footwear with foot manikins from other laboratories.
Keywords: noge; obutev; preizkušanje; potenje; modeli